The Pulsed Electric Field Assisted-Extraction Enhanced the Yield and the Physicochemical Properties of Soluble Dietary Fiber From Orange Peel - Fan, Rui; Wang, Lei; Fan, Jingfang; Sun, Wanqiu; Dong, Hui (Frontiers in Nutrition, 2022)
The study aimed to investigate the effects of pulsed electric fields (PEF)-assisted extraction on the yield, physicochemical properties and structure of soluble dietary fiber (SDF) from orange peel. The results showed that the maximal yield of SDF obtained at temperature of 45℃ with the electric field intensity of 6.0 kV/cm, pulses number of 30, and time for 20 min which the extraction yield increased over 100 % compared with the untreated one, and SDF treated with PEF showed the higher water solubility, water-holding and oil-holding capacity, swelling capacity, emulsifying activity, emulsion stability, foam stability and higher binding capacity for Pb2+, As3+ and Cu2+ and higher peak temperature (130.5 ℃ vs. 122.6 ℃) , which resulted from the higher viscosity due to PEF treatment. Compared with the untreated orange peel, the SDF obtained with PEF exhibited the stronger antioxidant activities, which was due to its smaller molecular weight (189 k Da vs. 512 k Da). In addition, scanning electron micrograph images demonstrated that the surface of PEF-SDF was rough and collapsed. Overall, it was suggested that PEF treatment could improve the physicochemical properties of SDF from the orange peel and would be the potential extraction technology with high-efficiency.